Fractionation of catfish protein hydrolysates using ultrafiltration membrane - Novin, Donya (2014)
Membrane filtration process of different protein solutions has attracted the interest of many recent researchers. By manipulating the operating parameters it can be an efficient process to concentrate, separate and purify with the purpose of increasing the biological activity of proteins. The objective of this study was to investigate the effect of operating parameters experimentally, such as transmembrane pressure (TMP), pH, ionic strength and feed concentration on permeate flux and transmission of protein hydrolysates. Regenerated cellulose (RC) membranes of 5kDa and 10 kDa were employed in dead-end ultrafiltration mode. The selection of best parameters was based on the highest transmission considering the appropriate amount of permeate flux. The protein hydrolysates were prepared by enzymatic hydrolysis of Catfish muscle. The enzymatic hydrolysis was performed at pH 9, 50˚C, 2.5% w/v of substrate to buffer and 1% enzyme. The degree of hydrolysis of two selected samples at time of 0.5 h and 5 h hydrolysates for filtration process were 44.88 % and 58.72 % respectively. The two selected samples of hydrolysates (0.5 h and 5 h) were used to compare the antioxidant activity as well as the separation efficiency of hydrolysates based on their molecular weights. Screening for the optimum parameters showed that the highest transmission was achieved at pH 7, pressure of 1.5 bar, 0.15 M of NaCl and 1.5 mg/ml concentration of feed for 0.5 h hydrolysate. The transmission was found to range between 64.54%- 88.89% for 5 kDa and 84.62%-93.14%for 10 kDa membrane. For 5 h hydrolysate, the highest transmission was achieved at pH 5.1, pressure of 2 bar, 0.15 M of NaCl and feed concentration of 1.5 mg/ml. The transmission ranged between 52.96% - 56.37%for 5 kDa and 74.70%-77.76% for 10 kDa. The best value of antioxidant activity from DPPH-scavenging assay was 69.04% for 10 kDa fraction; and from metal ion chelating assay was 74.06% for fraction of 10 kDa for 0.5 h hydrolysate. The highest absorbance of 0.44±0.011was obtained from reducing power assay for 5 h hydrolysate using 5 kDa membrane. The results of hydrolysis and ultrafiltration process showed that by manipulating and appropriate selection of the operating parameters, the degree of hydrolysis and the yield of filtration process (permeate flux and transmission of protein hydrolysates)can improve. Also, the results showed the ffectiveness of ultrafiltration to achieve higher antioxidant activity based on the molecular weight separation.